Model Matematis Lalu Llintas Pada Ruas Jalan 4/2 UD Jalan Diponegoro - Yoga Kartiwi, Diana Williani; Putra, Sasana; Herianto, Dwi; Sulistyorini, Rahayu (Jurnal Rekayasa Sipil dan Desain (JRSDD), 2023)
Jalan Diponegoro is an undivided 4-lane 2-way road that connects the urban center with residential areas in Bandar Lampung City. The traffic jam that occurs on Jalan Diponegoro when the traffic light is red often causes queues of vehicles, especially during peak hours. The purpose of this study is to determine the pattern of mathematical relationships between speed (S), current (V), and density (D) made using the Greenshiled Model. Based on the EKR headway ratio, the results obtained from the calculation of the Greenshields Model for morning observations Sff = 24.61 km/hour; Dj = 32.16 SKR/km; VM = 197.70 SKR/hour; BC = 12.31 km/hour; and DM = 16.08 SKR/km. Whereas in the afternoon observation, the value of Sff = 29.45 km/hour, Dj = 47.50 SKR/km, VM = 349.74 SKR/hour, SM = 14.72 km/hour, and DM = 23.75 SKR/ km. Keywords : Volume, Speed, Density, Model Greenshield.